Kepuasan Kerja Pegawai Di Puskesmas Bontomarannu Gowa - Ali Imran; Shermina Oruh; Muslimin S; Rusnita Rusnita; Adriyani Adam (Direktorat Politeknik Kesehatan Makassar, 2024)
In order to improve the level of public health. There are many things that need to be considered, one of which is considered to have a quite important role, namely health care. So that the desired health management can be carried out well. There are many conditions that must be met, one of which is that the health service must have good quality values. Performance will be directed at all efforts carried out using human resources and supporting work facilities, thus all ideas and policies are taken to increase the company's work productivity. Efforts to compress existing resources to make something happen optimally by combining sources and results in an optimal form, human labor, in addition to facilities and other production sources are resources that must be utilized fully and purposefully. This research aims to determine the relationship between competence, work discipline and satisfaction with employee performance. The type of research used is an observational study with a cross sectional study approach. The population of this study was 49 civil servants, and the sample in this study was a total population of 49 people. The results of the research show that there is a relationship between competency, work discipline and employee satisfaction with employee performance at the Bontosunggu Community Health Center, Gowa Regency. Bontomarannu Community Health Center can prioritize developing the work competencies of its employees through training, workshops and further education as well as providing rewards for employees who excel. This will help improve the quality of service provided by employees. The conclusion of this research is that there is a relationship between work competency, work discipline, job satisfaction and employee performance at the Bontomarannu Community Health Center, Gowa Regency. Keywords : competency; discipline, satisfaction, performance